Automations in the Screening of Autism Spectrum Disorder - Pandkar, Chakor; Pensalwar , Rakshit; Chakravarty , Anshuman; Bhairavkar , Aditya (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
The Autism Spectrum Disorder (ASD) is known to be characterized by decreased social interactions to stimuli, diffculties in communication, repetitive behaviors and physical movements. Since it affects different individuals differently and to different extents, it is very challenging to diagnose and differentiate from other neurodevelopmental disorders. Research shows that early intervention can be very bene cial in the long term as the affected individuals’ symptoms can be reduced to a great extent , but the lack of awareness and objective diagnostic tools makes it diffcult to diagnose at an early age. In this paper we explore the various innovations made in automating the screening process by listing the demerits of the subjective existing diagnosis systems and also surveys and complies the various eye gazing, voice prosody, wearable IoT modules, their contributions and their impacts in making the diagnosis process of Autism Spectral Disorder more objective and efficient.